Low-Power Red and Infrared Laser Effects on Cells Deficient in DNA Repair - Fonseca Iwahara, Lucas Kiyoshi; Paoli, Flavia; Fonseca, Adenilson Souza (Journal of Lasers in Medical Sciences, 2019)
Introduction: Low-level lasers are successfully used to prevent and treat diseases in soft oral and bone tissues, particularly diseases in oral cavity caused by chemotherapy and radiotherapy in oncology. However, controversy exists as to whether these lasers induce molecular side effects, mainly on DNA. The aim of this work was to assess the effects of low-power lasers on mutant Escherichia coli cells in DNA repair. Methods: Escherichia coli wild type cultures as well as those lacking recombination DNA repair (recA-) and la SOS responses (lexA-) irradiated with lasers at different energy densities, powers, and emission modes for cell viability and morphology assessment were used in this study. Results: Laser irradiation: (i) did not affect cell viability of non-mutant and lexA- cells but decreased viability in recA- cultures; (ii) altered morphology of wild type and lexA, depending on the energy density, power, emission mode, and wavelength. Conclusion: Results show that low-level lasers have lethal effects on both recombination DNA repair and SOS response bacterial cells but do not induce morphological modifications in these cells.